Stilbene polyphenols in the brown red wood of Vitis vinifera cv. Sangiovese affected by "esca proper"* - Carmine AMALFITANO; Diana AGRELLI; Alessandro ARRIGO; Laura MUGNAI; Giuseppe SURICO; Antonio EVIDENTE (Phytopathologia Mediterranea, 2011)
A number of stilbene polyphenols, dimers, trimers and tetramers of resveratrol (viniferins), which are typical Vitaceae metabolites, were extracted from asymptomatic wood (AW) and symptomatic brown-reddiscoloured wood (BRW) of Vitis vinifera cv. Sangiovese affected by “esca proper”, the trunk disease caused by the fungal complex Phaeomoniella chlamydospora, Phaeoacremonium aleophilum and Fomitiporia mediterranea. Resveratrol and the same types of viniferins were found in both AW and BRW, with the exception of α-viniferin, which was only detected in AW, and ampelopsin B, only in BRW. The total concentration of stilbene polyphenols was higher in symptomatic wood (3.7% in BRW vs 1.2% in AW). The absolute variationsin molar concentrations of each stilbene polyphenol (i) between BRW and AW (Δi = CiBRW - CiAW), were higherfor ε-viniferin and resveratrol than the other compounds, while the relative variations (Δi/CiAW), were lower for ampelopsin H and isohopeaphenol, and higher for ampelopsin B, hopeaphenol, ampelopsin A, leachianol F and G, pallidol and ε-viniferin (in descending order), than the relative variation for resveratrol. Aspects relating to the biosynthesis of stilbene polyphenols and their role in the host-esca pathogen interaction are discussed.